(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article deals with the issues of design and its influence on the development of ecotourism in Belarus through the creation of unique impressions and effective solutions. The impression industry tends to emphasize emotional and personal interaction with tourists, which contribute to the strengthening of the tourism industry and improving the level of service, both to the population of the republic and foreign guests. The importance of integrating design into ecotourism organization is emphasized to improve the efficiency and competitiveness of the industry. The study also revealed that the use of design solutions contributes to the preservation of natural resources and promotes the propaganda of careful attitude to nature. It is concluded that design is a powerful tool for shaping unique tourism products and enhancing the experience of visiting eco-friendly destinations.